“We Reach to People Through Different Means”: Factors That Influence HIV Counseling and Testing Among Religious People in Lilongwe, Malawi - Tifiness Mary Banda Kamanga; Lusungu Chirambo; Martha Valeta; Alinane Linda Nyondo-Mipando (SAGE Open, 2023)
A descriptive qualitative study among 12 religious leaders and 10 members from seven different religions using in-depth interviews was conducted to explore the factors that influence HIV testing among religious people in the area of Traditional Authority Chitukula, Lilongwe district. Participants and sites were purposively selected and all interviews were recorded using a digital recorder, then transcribed and translated into English. Data were analyzed using a thematic approach. The study showed that prayer has a prominent role in the management of HIV and AIDS. The barriers to HIV testing include a belief in faith healing, the rules of a specific church, and a perception of a low risk of HIV infection among religious people. Interventions that could promote HIV testing include the implementation of HIV self-testing, mobile and or door-to-door HIV services, church-based HIV testing services, and facility-based services that are integrated with other services to preserve privacy. Religious platforms can be leveraged in the delivery of HIV testing services. The promotion of religious-based prevention interventions needs to consider the foundations and beliefs of each religion and be able to contextualize the methods which can be achieved by continuous dialogue and support from religious leaders.